Sex-specific digestive performance of mussels exposed to warming and starvation - Shang, Yueyong; Wei, Shuaishuai; Chang, Xueqing; Mao, Yiran; Dupont, Sam; Kar-Hei Fang, James; Hu, Menghong; Wang, Youji (Frontiers in Physiology, 2022)
As global climate change has dramatically impacted the ocean, severe temperature elevation and a decline in primary productivity has frequently occurred, which has affected the structure of coastal biomes. In this study, the sex-specific responses to temperature change and food availability in mussels were determined in terms of digestive performance. The Thick Shell Mussels Mytilus coruscus (male and female) were exposed to different temperature and nutritional conditions for 30 days. The results showed that the digestive enzymes of mussels were significantly affected by temperature, food, sex and their interactions. High temperature (30°C) and starvation significantly decreased amylase, lysozyme and pepsase activities of female mussels, while trypsin and trehalase did not change significantly at the experimental end. The activity of amylase, trypsin and trehalase was significantly reduced in males at high temperature (30°C) under starvation treatment, but high temperature (30°C) elevated pepsase. Unsurprisingly, starvation caused the reduction of lysozyme and pepsase under 25°C in males. Amylase, lipase and trehalase were higher in female mussels compared with males, while the enzymatic activities of lysozyme, pepsase and trypsin were higher in male mussels than females. Principal component analysis showed that different enzyme activity indexes were separated in male and female mussels, indicating that male and female mussels exhibited significantly different digestive abilities under temperature and food condition change. The study clarified sex-specific response difference in mussel digestive enzymes under warming and starvation, and provided guidance for the development of mussel aquaculture (high temperature management and feeding strategy) under changing marine environments.